Effect of Pd and Au Sensitization of Bath Deposited Flowerlike TiO2 Thin Films on CO Sensing and Photocatalytic Properties. (28th July 2013) - Singh, Ashok K.; Patil, S. B.; Nakate, Umesh T.; Gurav, K. V.
Abstract : TiO2 thin films having flower structure with nanopetals are deposited by chemical bath deposition (CBD) method. Deposited TiO2 films are formed in pure anatase phase as confirmed by X-ray diffraction (XRD) analysis. Deposited films are used for detection of environmental hazardous carbon monoxide (CO) gas and photocatalytic (PC) degradation of malachite green (MG) dye. Effect of Pd and Au catalysts sensitization on gas sensing as well as PC degradation properties is investigated. The use of catalyst led to enhancement in the gas sensitivity and reduction in the operating temperature as well as response and recovery times. The Au sensitized film showed better CO sensing performance and PC efficiency in comparison to unsensitized and Pd sensitized TiO2 thin films. For Au sensitized film, gas sensitivity, response time, and recovery time are found to be 32% (14% for TiO2 ), 80 s, and 100 s, respectively, and PC efficiency is found to be 26.6% (16.9% for TiO2 ).